The Influence Of Capital, Working Hours, And Location On The Income Level Of Nganjuk Wage Market Traders, Nganjuk District - Muhammad Bawono; Yendra Okta Novian; Indra Dekrijanti; Rendi Dwi Apriansa (IAEI, 2023)
A market is where goods are bought and sold with more than one seller, whether referred to as a shopping centre, traditional market, shop, mall, plaza, trade centre, or other names. This research aims to analyze how much capital, working hours and location influence traders' income. Random sampling method. The sample in this research was 79 traders, and then analysis was carried out on the data obtained using quantitative data analysis. Quantitative analysis includes validity and reliability tests, classical assumption tests, multiple regression analysis, hypothesis testing via t-test and f-test, and analysis of the coefficient of determination (R2). Hypothesis testing using the t-test shows that the three independent variables studied are proven to have a significant partial effect on the dependent variable of trader income. Then, through the F test, it can be seen that the three independent variables examined simultaneously affect the dependent variable of trader income. The adjusted R2 figure is 0.653, indicating that 65.3% of the trader's income variable can be explained by the three independent variables in the regression equation. Meanwhile, the remaining 34.7% is explained by other variables outside the two variables used in this research.